Anomalous fading correction for dosimetry at small time scales. (May 2019) - Sahai, Manish K.; Bakshi, A.K.; Datta, D.
Abstract: In several cases after glow from an exposed sample shows deviation from power law decay of luminescence, I α t -k where I is luminescence intensity, t is time of observation and k is a constant. It is shown that the non linearity is the general feature of afterglow and linear graphs observed in experiments or simulation are, in general, an artefact of time scale of observation. Present study also suggests curve fitting functions for afterglow. Study of afterglow is important for applying fading corrections in various domains of dosimetry. Highlights: Work establishes that non linearity is general feature of afterglow. It discusses about few factors which can effect advent of non linearity in log(I)-log(st) graph. Suggests curve fitting functions for afterglow.